Correction: Cationic conjugated polymer-based FRET aptasensor for label-free and ultrasensitive ractopamine detection. Issue 20 (22nd April 2022) - Fu, Xuancheng; Dong, Wei; Liu, Chang; Han, Jing; Huang, Chengzhi
Abstract : Correction for 'Cationic conjugated polymer-based FRET aptasensor for label-free and ultrasensitive ractopamine detection' by Xuancheng Fu et al., RSC Adv., 2022, 12, 10911–10914, ; https://doi.org/10.1039/d2ra00574c .